Optimizing the nitrogen configuration in interlayer-expanded carbon materials via sulfur-bridged bonds toward remarkable energy storage performances. Issue 18 (7th April 2022) - Li, Zhiqiang; Yang, Yang; Ding, Gaohui; Wei, Lingzhi; Yao, Ge; Niu, Helin; Zheng, Fangcai; Chen, Qianwang
Abstract : Herein, we demonstrate that C–S–C bonds can significantly enlarge the interlayer spacing of carbon materials and change the N-doping configuration in graphene layers. Abstract : Carbon materials are promising anodes for potassium ion batteries (PIBs) due to their high conductivity, structural stability, and abundant resources, while their capacity and rate capability are still unsatisfactory for the requirements of high-performance PIBs. The synergy of enlarging interlayer spacing and increasing absorption sites is vital in achieving the application of carbon materials in PIBs. Herein, we demonstrate that C–S–C bonds can significantly enlarge the interlayer spacing of carbon materials and change the nitrogen-doping configuration in graphene layers. The optimized sulfur/nitrogen co-doped carbon materials (S/N-CMs) achieve a high-level edge-N doping (87.9%) and expanded interlayer spacing (0.41 nm), and display an ultrahigh reversible capacity of 578 mA h g −1 at 0.1 A g −1 after 200 cycles. They also achieve an ultra-long cycle life of 249 mA h g −1 at 5 A g −1 after 10 000 cycles with a capacity fading of 0.0024% per cycle. Theoretical calculations further verify that C–S–C bonds can not only expand the interlayer spacing of graphitic layers, but also cooperate with edge-N atoms to improve the adsorption ability of K + in carbon materials.